2017
DOI: 10.1128/jcm.01881-16
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Metagenomic Next-Generation Sequencing during an Investigation of Hospital-Acquired Human Parainfluenza Virus 3 Infections

Abstract: Metagenomic next-generation sequencing (mNGS) is increasingly used for the unbiased detection of viruses, bacteria, fungi, and eukaryotic parasites in clinical samples. Whole-genome sequencing (WGS) of clinical bacterial isolates has been shown to inform hospital infection prevention practices, but this technology has not been utilized during potential respiratory virus outbreaks. Here, we report on the use of mNGS to inform the real-time infection prevention response to a cluster of hospital-acquired human pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 31 publications
1
60
0
Order By: Relevance
“…In our experience, and as recently reported, NGS offers a significantly higher discriminatory value as an epidemiologic tool, and can be used to gather real-time information and identification of transmission linkages to assist in infection prevention in these highly immunocompromised patients (9,10). A challenge going forward will be developing bioinformatics tools which will allow this sequencing information to be available to clinical providers in a rapid and actionable timeframe.…”
Section: Discussionsupporting
confidence: 68%
“…In our experience, and as recently reported, NGS offers a significantly higher discriminatory value as an epidemiologic tool, and can be used to gather real-time information and identification of transmission linkages to assist in infection prevention in these highly immunocompromised patients (9,10). A challenge going forward will be developing bioinformatics tools which will allow this sequencing information to be available to clinical providers in a rapid and actionable timeframe.…”
Section: Discussionsupporting
confidence: 68%
“…The benefit of the protocol is the minimal hands-on time, low cost given the dilutability of the transposase, ease of dual-indexing, and direct compatibility with Illumina sequencers. The protocol can be performed in as little as 4-6 h and is amenable to automation (Greninger et al, 2017b(Greninger et al, , 2017c. Variants include the use of additional PCR cycles or amplification prior to tagmentation.…”
Section: A Metastable Approachmentioning
confidence: 99%
“…A first report on the use of metagenomics NGS for the investigation of a nosocomial outbreak by parainfluenza virus 3 was published by Greninger et al in 2016 . By Bayesian phylogenetic analysis, these authors demonstrated that two strains causing HAI have the same sequence confirming the hypothesis of a possible transmission within the medical ward where the two patients were admitted.…”
Section: Phylogenetic Analysis Of Whole‐genome Sequencing For Viral Nmentioning
confidence: 99%
“…By Bayesian phylogenetic analysis, these authors demonstrated that two strains causing HAI have the same sequence confirming the hypothesis of a possible transmission within the medical ward where the two patients were admitted. Authors concluded that NGS and WGS represent important tools for pathogen transmission investigation and a significant advance in clinical care providing pathogen detection with high resolution and reliability …”
Section: Phylogenetic Analysis Of Whole‐genome Sequencing For Viral Nmentioning
confidence: 99%